Effect of Rhizoma Drynariae on differential gene expression in ovariectomized rats with osteoporosis based on transcriptome sequencing - Su, Hui; Xue, Haipeng; Gao, Shang; Yan, Binghan; Wang, Ruochong; Tan, Guoqing; Xu, Zhanwang; Zeng, Lingfeng (Frontiers in Endocrinology, 2022)
Osteoporosis is increasingly becoming a serious problem affecting the quality of life of the older population. Several experimental studies have shown that Chinese medicine has a definite effect on improving osteoporosis. Based on transcriptome sequencing, we analyzed the differential gene expression and mechanism of the related signaling pathways. Fifteen rats were randomly divided into an experimental group, a model group, and a sham surgery group. The rat model for menopausal osteoporosis was established using an ovariectomy method. One week after modeling, the experimental group was administered 8.1 g/kg of Rhizoma Drynariae, whereas the model and sham groups received 0.9% saline solution twice daily for 12 weeks. Subsequently, the rats were sacrificed, and the left femur of each group was removed for computerized tomography testing, while right femurs were used for hematoxylin and eosin staining. High-throughput RNA sequencing and functional and pathway enrichment analyses were performed. Comparing the gene expression between the experimental and model groups, 149 differential genes were identified, of which 44 were downregulated and 105 were upregulated. The criteria for statistical significance were |log2 Fold Change| > 1 and P < 0.05. Gene ontology analysis showed that the differentially expressed genes were enriched in cell component terms such as cell part and outer cell membrane part, and the genes were associated with cell process, biological regulation, metabolic processes, DNA transcription, and catalytic activity. Enrichment analysis of Kyoto Encyclopedia of Genes and Genomes pathways showed significantly enriched pathways associated with systemic lupus erythematosus, herpes simplex infection, circadian rhythm, vascular smooth muscle contraction, the AGE-RAGE signaling pathway in diabetic complications, and the TNF, Apelin, and Ras signaling pathways. Our results revealed that the Npas2, Dbp, Rt1, Arntl, Grem2, H2bc9, LOC501233, Pla2g2c, Hpgd, Pde6c, and Dner genes, and the circadian rhythm, lipid metabolism, inflammatory signaling pathway, and immune pathways may be the key targets for traditional Chinese medicine therapy of bone fragment repair in osteoporosis.